Carcinoma escamoso oral: análise retrospectiva de 185 casos - Monti, Lira Marcela [UNESP] (2010)
The squamous cell carcinoma is the most common malignancy in the oral cavity, representing over 90% of cancers in this region. This study aimed to conduct an epidemiological study of oral squamous carcinoma cases diagnosed by the Department of Pathology, Department of Pathology and Clinical Propaedeutics in the Dentistry Faculty of Araçatuba - UNESP, in the period between 1995 and 2005. 185 cases were studied, it was observed that the oral floor and tongue were the sites most affected, with predominance in males, white race and aged between 41 and 60 years, noting that the majority of patients were smokers. Knowledge of these data is important for the dental surgeon to act preventively, contributing to early diagnosis of cancer.